Ministry of Tourism Decree No. 99 of the year 2017 Issued on 14/2/2017 = وزارة السياحة قرار رقم 99 لسنة 2017 صادر بتاريخ 14/2/2017 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic